A phosphodiesterase-4 inhibitor reduces lung inflammation and fibrosis in a hamster model of SARS-CoV-2 infection - Kolloli, Afsal; Ramasamy, Santhamani; Kumar, Ranjeet; Nisa, Annuurun; Kaplan, Gilla; Subbian, Selvakumar (Frontiers in Immunology, 2023)
The Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) infection involves pulmonary inflammation that can progress to acute respiratory distress syndrome, a primary cause of lung damage/fibrosis in patients with Coronavirus Disease-2019 (COVID-19). Currently, there is no efficacious therapy available to alleviate lung fibrosis in COVID-19 cases. In this proof-of-concept study, we evaluated the effect of CC-11050, a small molecule phosphodiesterase-4 inhibitor, in dampening lung inflammation and fibrosis in a hamster model of SARS-CoV-2 infection. Following intranasal inoculation with SARS-CoV-2/WA- 1/2000 strain, hamsters were treated with CC-11050 or placebo by gavage from day-1 until day-16 post-infection (dpi). Animals were monitored for body weight changes, virus titers, histopathology, fibrotic remodeling, cellular composition in the lungs between 2 and 16 dpi. Results showed significant reduction in lung viral titer with concomitant reduction in inflammation and fibrotic remodeling in CC-11050 treated hamsters compared to untreated animals. The reductions in immunopathologic manifestations were associated with significant downregulation of inflammatory and fibrotic remodeling gene expression, reduced infiltration of activated monocytes, granulocytes, and reticular fibroblasts in CC-11050 treated animals. Cellular studies indicate a link between TNF-α and fibrotic remodeling during CC-11050 therapy. These findings suggest that CC-11050 may be a potential host-directed therapy to dampen inflammation and fibrosis in COVID-19 cases.